2017
DOI: 10.1021/acs.est.7b00987
|View full text |Cite
|
Sign up to set email alerts
|

Proteins and Amino Acids in Fine Particulate Matter in Rural Guangzhou, Southern China: Seasonal Cycles, Sources, and Atmospheric Processes

Abstract: Water-soluble proteinaceous matter including proteins and free amino acids (FAAs) as well as some other chemical components was analyzed in fine particulate matter (PM) samples collected over a period of one year in rural Guangzhou. Annual averaged protein and total FAAs concentrations were 0.79 ± 0.47 μg m and 0.13 ± 0.05 μg m, accounting for 1.9 ± 0.7% and 0.3 ± 0.1% of PM, respectively. Among FAAs, glycine was the most abundant species (19.9%), followed by valine (18.5%), methionine (16.1%), and phenylalani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
93
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(113 citation statements)
references
References 79 publications
15
93
5
Order By: Relevance
“…More recent studies suggested that FAAs in aerosols might be released by direct photolysis (UV radiation), photocatalytic hydrolysis, and enzyme‐based hydrolysis from proteins/peptides (CAAs). For instance, Song et al () found that both proteins and total FAAs showed significant correlations with O 3 in PM2.5. Similarly, a linear correlation is also observed for FAA concentrations with O 3 in Research Triangle Park, USA (Samy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies suggested that FAAs in aerosols might be released by direct photolysis (UV radiation), photocatalytic hydrolysis, and enzyme‐based hydrolysis from proteins/peptides (CAAs). For instance, Song et al () found that both proteins and total FAAs showed significant correlations with O 3 in PM2.5. Similarly, a linear correlation is also observed for FAA concentrations with O 3 in Research Triangle Park, USA (Samy et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is an allergic disease, and there are several reports on allergic proteins originating from pollen and fungi in outdoor air [ 6 , 7 ]. In addition, various materials such as animal dander, as well as activities such as the combustion of organic materials, are also potential sources of protein in outdoor air [ 8 , 10 , 21 , 22 ]. Kang et al analyzed the protein and other constituents in airborne particles collected in Hefei, China, and concluded that anthropogenic activities and biomass combustion were the main sources of protein in the outdoor air in the study area [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reference optical length of this cell was determined to be 6.2 mm according to the sample volume and the size of the well (internal diameter-6.40 mm). Based on the reference value, the EOL for the sample test in microfluidic chips could be calculated according to eqn (3). The EOL can also be used as an inspection indicator of stray light.…”
Section: Equivalent/specific Optical Path Lengthmentioning
confidence: 99%
“…Absorbance measurement is a frequently used quantification method for various analysis applications such as immunoassays, 1,2 protein quantification, 3,4 detection of blood glucose, 5 assessment of environmental quality, [6][7][8] etc. Compared with absorbance analysis in 1 ml detection cells or 96-well plates, the microfluidic-based assay has attracted lots of attention due to the reduced sample consumption and the miniaturized system.…”
Section: Introductionmentioning
confidence: 99%